analisis The Implications of Moving the National Capital for the Configuration of Indonesian Political Power in the Era of Leadership Transition from Jokowi to Prabowo - Naila Kamila (POLTRANS: Journal of Politics and Social Transformation, 2025)
The relocation of the National Capital (IKN) from Jakarta to the Indonesian archipelago in East Kalimantan is not merely a technocratic policy, but rather a strategic manoeuvre with a significant impact on Indonesia's political configuration, particularly during the transition from President Joko Widodo to Prabowo Subianto. This study examines how the relocation of the IKN affects the distribution of power, elite alliances, and the role of civil society. Using a qualitative approach based on literature studies and document analysis, the main findings indicate a shift in power from the central elite in Jakarta to local actors and oligarchs involved in the development of the IKN. New political alliances are forming, but they tend to be pragmatic rather than ideologically driven. On the other hand, the power of civil society is beginning to emerge, although its space for participation remains limited, and it is often marginalised. The leadership transition is a crucial context because it determines the sustainability or change in direction of the IKN project. This study emphasises that the development of the new capital reflects a contestation of power and is not politically neutral. Thus, the IKN project is a crucial arena for assessing the extent to which democracy and political participation are truly realised in Indonesia's national development process.